160k views
0 votes

5x-6=3x-8



Thx

2 Answers

5 votes

Answer:


5x - 6 = 3x - 8


= > 5x - 3x = ( - 8 ) + 6


= > 2x = -2


= > x = ( - 2)/(2)


= > x = - 1

Therefore the value of x is -1

Hope it helps you!!

#IndianMurga

User UVM
by
5.1k points
2 votes


= \: \: \: x = - 1

step by step Step-by-step explanation:

move the terms


5x - 6 = 3x - 8

collect like terms


5x - 3x = - 8 + 6

divide both sides


2x = - 2

there for the equation has been solved


= \: \: \: x = - 1

hope it helps

#carry on learning

User Paul Hoenecke
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.